Music and change in Nain, Nunatsiavut: More White does not always mean less Inuit - Artiss, Tom (Études/Inuit/Studies, 2014)
This paper focuses on Inuitized Western music in Nain, Labrador, as part of a broader look at Inuit responses to change. Drawing on interviews and sustained ethnographic research, I show how a relaxing of strict socio-musical categories coincided with a decline in Moravian missionary influence in the second half of the 20th century. A notable indifference to musical difference is, I suggest, consistent with an Inuit equanimity toward environmental forces of change that cannot be helped (ajunamat). I then give reasons why discursive imbalances are a continued concern and show how the effects of sustained colonial and missionary activity (hybridities, mixtures, overlaps, co-presences) do not always produce the emotional and psychic dissonances sometimes associated with postcolonial ambivalence. Ultimately, I propose thinking of Inuitized Western musical forms as visible protrusions of a much deeper substrate of affective continuities and that such inherited ways of being in the world can remain constant even while specific cultural forms may change.